Principles of urban retail planning and development - Gibbs, Robert J. (Chichester, England : John Wiley & Son, Inc., 2012)
The retail environment has evolved rapidly in the past few decades, with the retailing industry and its placement and design of "brick-and-mortar" locations changing with evolving demographics, shopping behavior, transportation options and a desire in recent years for more unique shopping environments. Written by a leading expert, this is a guide to planning for retail development for urban planners, urban designers and architects. It includes an overview of history of retail design, a look at retail and merchandising trends, and principles for current retail developments. Principles of Urban Retail.
Chapter 1. Retailing Fundamentals -- Chapter 2. Retailer Business Models -- Chapter 3. Retail Anchors -- Chapter 4. Downtown Commerce: Challenges and Opportunities -- Chapter 5. Economically Sustainable Commercial Urbanism -- Chapter 6: Shopping Center Built-Form Types -- Chapter 7. Planning and Urban Design -- Chapter 8. Parking -- Chapter 9. Store Planning and Visual Merchandising -- Chapter 10. Retail Development Finance.
Includes bibliographical references and index.
Keywords: SHOPPING CENTERS -- UNITED STATES -- PLANNING